Innovative Hybrid Mass Damper for Dual-Loop Controller. (15th January 2019) - Chesné, S.; Inquieté, G; Cranga, P.; Legrand, F.; Petitjean, B.
Highlights: Innovative transducer for a specific control law. The work contains numerical and experimental parts. Academic setup for the understanding of various physical phenomena. Full scale validation on a real helicopter. Abstract: The paper presents a new dual transducer and its associated control law. It aims to increase the efficiency of a traditional passive damped electromagnetic resonator by controlling its mass response actively. The design aspects of the so-called Dual-Loop Controller (DLC) for Hybrid Mass Damper (HMD) are presented and discussed. The control law attempts to modify a Tuned Mass Damper (TMD) to use it as an Active Mass Damper (AMD), with the objective of combining the best of the two technologies by actively increasing the performance of the passive device. Based on an optimally tuned passive device, the resulting system is fail-safe. The conception of the new dual transducer used as an HMD, designed specifically for this control law, is detailed. The hybrid device is experimentally validated both on a laboratory setup and on a real helicopter.